Increased Arterial Stiffness is an Independent Predictor of Renal Function Decline in Patients With Type 2 Diabetes Mellitus Younger Than 60 Years - Fountoulakis, Nikolaos (J Am Heart Assoc, 2017)
BACKGROUND: The objective of this study was to evaluate whether aortic pulse wave velocity (Ao‐PWV) predicts estimated glomerular filtration rate (eGFR) decline in patients with type 2 diabetes mellitus. METHODS AND RESULTS: This prospective single‐center cohort study investigated 211 type 2 diabetes mellitus patients with eGFR ≥45 mL/min with a baseline mean age of 60.1 years (range, 30–82 years). The mean±SD baseline eGFR was 85±26.1 mL/min. We divided the cohort into 2 groups above (n=117, “older”) and below (n=94, “younger”) the mean age to evaluate whether Ao‐PWV predicted progression of kidney disease differentially in older and younger patients. The primary end point was reaching a final eGFR below the median for the age group and an eGFR fall ≥1 mL/min per year. Median follow‐up was 9 years (range, 3–11 years) and ≈50% of patients in both groups reached the primary end point. In older patients, Ao‐PWV was similar in those who did and did not reach the primary end point. By contrast, younger patients who reached the primary end point had a higher Ao‐PWV at baseline compared with those who did not (10.8 m/s versus 9.5 m/s, respectively; mean difference of 1.36 m/s [95% CI, 0.38–2.33], P=0.007). Ao‐PWV was an independent predictor of the primary end point (incident risk ratio, 1.09; 95% CI, 1.02–1.18) after adjustment for traditional risk factors only in younger patients (P=0.02). A 1m/s increase in Ao‐PWV was associated with a mean fall in eGFR of 2.1 mL/min per year (95% CI, 0.09–4.1) independent of other risk factors in younger patients (P=0.04). CONCLUSIONS: Ao‐PWV predicts eGFR decline, before the onset of advanced renal dysfunction, and is a potential target for renoprotection in younger patients with type 2 diabetes mellitus.